Ameloblastoma - An experience of 31 cases - Ud Din, Qiam; Sherani, Ayub Shah (Journal of Postgraduate Medical Institute, 2011)
this is a review of 31 cases of ameloblastoma seen and managed at the oral and Maxillofacial surgical unit, Khyber College of Dentistry and at a private practice over a 10 years period. A male preponderance was found, with peak presentation in both the cortical plates. Currettage and skimming of the healthy bone in unilocular cases of the mandible still holds good provided the patient is followed up for long period. Resection of the lesion with dento alveolar bone and preservation of the lower border of the mandible is effective conservative management in patients with multilocular ameloblastoma having an intact lower border. Where practicable, bone grafting should be done immediately to avoid the common complications of displacement of principle segments and occlusal disharmony that occur when grafting is delayed.